Photos that Mrs. Sheppard had packed up on the floor of her home while she waited for her living-room wall to be completed - Skinner, Gail M. (1978)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « Description of a house at West Bay ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "Description of a house at West Bay".